The Examination of an Improved Analogue Method for Gridded Temperature Variation Reconstruction - Xuezhen Zhang; Xiaoyue Yan; Maowei Wu; Jingyun Zheng (International Journal of Climatology, 2025)
The analogue method (AM) is an approach for climate field reconstruction through combining proxy data and modelling data. This study improved the quantitative method of analogue pattern through considering the spatial distribution non‐uniformity of proxy data (i.e., k p term) and temperature changes capturing ability of proxy data ( v p term). Meanwhile, this study carries out pseudo‐proxy experiments on temperature variations in the eastern Central Asia‐East Asia region from 1902 to 1992 to examine the feasibility of the improved AM. The reconstruction results derived from improved AM match well with the instrumental data in terms of the temporal–spatial characteristics of temperature variation, with a correlations coefficient ( r ) of 0.5 ( p r = 0.54, 0.51, and 0.44 ( p r = 0.28 ( p r = 0.54, 0.50, and 0.35 ( p